Use of in-home stationary cycling equipment among parents in a family-based randomized trial intervention. Issue 10 (October 2018) - Rhodes, Ryan E.; Beauchamp, Mark R.; Blanchard, Chris M.; Bredin, Shannon S.D.; Warburton, Darren E.R.; Maddison, Ralph
Abstract: Objectives: The purpose of this study was to examine the use of home exercise equipment in the form of exergame cycling compared to a stationary recumbent bicycle ergometer in front of TV in the home over 3 months among parents of an intervention with their inactive children. The primary outcome was bike use (total weekly duration). Predictors of bike use in the form of theory of planned behavior and self-determination theory were also examined. Design: Randomized controlled trial. Method: Sixty eight parents of children aged 10–14 were randomized to either the exergame condition (n = 36) or the standard bike condition (n = 32). Weekly bike use was recorded in a log-book. Results: The exergame bike and a standard bike in front of a TV had similar use across three months ( p = .13, η p 2 = .02), which declined over time ( p < .01, η p 2 = .14). Parents who were active at baseline and had the intention to use the bikes were more likely to use the bikes ( p < .05). Furthermore, those who reported higher perceived control, intrinsic motivation, and affective attitude were more likely to use the bikes ( p < .05). Conclusions: The findings suggested that irrespective of modality, use of exercise equipment declined considerably for parents over three-months. Parents may also benefit from family physical activity interventions, but it depends on their physical activity status, how much they would enjoy using the equipment, and their overall perceived control over being physically active. Trial registration: clinicaltrials.gov #NCT01373762. Registered 1 June 2011.